Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Show that $$\sum_{k=0}^{n}\binom n k\frac{5^k}{5^k+1}\ge\frac{2^n\cdot 5^n}{3^n+5^n}$$

where $$\binom n k=\frac{n!}{k!(n-k)!}$$

share|cite|improve this question
up vote 7 down vote accepted

Note that the LHS is $$ (\ast)=\sum_{k=0}^n{n\choose k}\frac1{1+5^{-k}}=2^n\cdot\mathbb E\left(\frac1{1+5^{-S_n}}\right), $$ where the random variable $S_n$ is binomial $\left(n,\frac12\right)$. Since the function $x\mapsto\frac1{1+x}$ is convex on $x\geqslant0$, Jensen's inequality yields $$ (\ast)\geqslant\frac{2^n}{1+\mathbb E\left(5^{-S_n}\right)}. $$ Now, $S_n$ is distributed as $X_1+\cdots+X_n$ for some i.i.d. Bernoulli random variables $(X_k)_{1\leqslant k\leqslant n}$ such that $\mathbb P(X_k=0)=\mathbb P(X_k=1)=\frac12$. One gets $\mathbb E\left(5^{-X_k}\right)=\frac12\left(1+\frac15\right)=\frac35$ and, by independence, $\mathbb E\left(5^{-S_n}\right)=\left(\frac35\right)^n$. This proves the claim.

share|cite|improve this answer
    
Nice.:-D During my student years I studied much more analysis than the theory of probability. :-) – Alex Ravsky Jun 26 '13 at 20:24
    
It's nice, Thank you +1 – math110 Jun 27 '13 at 3:15

It seems that we can prove the inequality as follows: $$S=\sum_{k=0}^{n}\binom n k\dfrac{5^k}{5^k+1}=$$ $$\frac 12+\sum_{k=1}^{n}\binom n k\dfrac{1}{1+5^{-k}}=$$ $$\frac 12+\sum_{k=1}^{n}\binom n k\sum_{i=0}^\infty (-1)^i(5^{-k})^i=$$ $$\frac 12+\sum_{i=0}^\infty \sum_{k=1}^{n}\binom n k (-1)^i5^{-ki}=$$ $$\frac 12+\sum_{i=0}^\infty \sum_{k=1}^{n}\binom n k (-1)^i5^{-ik}=$$ $$\frac 12+\sum_{i=0}^\infty (-1)^i((1+5^{-i})^n-1).$$

Since the last series is alternating, its sum is greater than the sum of its four first members. Therefore $$S\ge \frac 12+(2^n-1)-\left(\left(\frac 65\right)^n-1\right)+\left(\left(\frac {26}{25}\right)^n-1\right)-\left(\left(\frac {126}{125}\right)^n-1\right)=$$ $$2^n-\left(\frac 65\right)^n+\left(\frac {26}{25}\right)^n-\left(\frac {126}{125}\right)^n+\frac 12.$$

Check when $$2^n-\left(\frac 65\right)^n+\left(\frac {26}{25}\right)^n-\left(\frac {126}{125}\right)^n\ge \frac{2^n\cdot 5^n}{3^n+5^n}.$$

After reducing both sides to the common denominator and simplifying we obtain the inequality $$650^n+390^n\ge 630^n+450^n+378^n.$$ But $$650^6>630^6+450^6+378^6,$$ thus the inequality holds for each $n\ge 6$.

It rests to check the initial inequality for $n\le 5$, which can be done straightforward.

share|cite|improve this answer
1  
It's nice! Thank you +1 – math110 Jun 26 '13 at 16:25
2  
The first term in line 2 should be $\frac 1 2$ instead of 1, is not so? – user64494 Jun 26 '13 at 17:18
1  
@user64494 Yes. Thanks. I'll correct this. – Alex Ravsky Jun 26 '13 at 18:01
1  
When the last term one keeps in an alternating series is positive, the sum of the series is smaller than the truncated sum, not larger. – Did Jun 26 '13 at 19:04
1  
@Did Thanks. I try to correct this. – Alex Ravsky Jun 26 '13 at 19:30

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.